Residual Stress Measurement of Used Mining Dump Truck Frame for Remanufacturing Purposes - Ferdiyanto, David; Sofyan, Nofrijon; Yuwono, Akhmad Herman; Dhaneswara, Donanta (National Research and Innovation Agency (BRIN), 2023)
Remanufacturing the main frame of a mining dump truck can save cost, energy, and materials in heavy equipment industries. It also can reduce CO2 emissions for environmental preservation to achieve sustainability. However, since the mainframe received a dynamic load during operation, it presumably leaves accumulated residual stresses in the frame. The residual stress, particularly tensile residual stress, stands out as a primary contributing factor to the initiation of cracks, which may ultimately result in failures. In this paper, the residual stress of the used mining dump truck main frame was identified by modeling simulation using FEA (finite element analysis) and actual measurement using a portable x-ray residual stress analyzer with the cos α method. The results showed that the weld area subjected to dynamic loads exhibited the highest tensile residual stress, reaching approximately +772 MPa. This specific region emerges as a critical area demanding attention during the remanufacturing process. The application of PWHT (post-weld heat treatment) at 400 °C for 1 hour effectively reduced residual stress on the weld joint, predominantly tensile residual stress, by more than 80%.